Spirituality and Prayer on Teacher Stress and Burnout in an Italian Cohort: A Pilot, Before-After Controlled Study - Chirico, Francesco; Sharma, Manoj; Zaffina, Salvatore; Magnavita, Nicola (Frontiers in Psychology, 2020)
Abstract Introduction: Teaching is a stressful profession that exposes workers to the risk of burnout. Techniques involving higher mental functions, such as transcendental meditation and prayer, have been used in stress and burnout prevention programs. In this study, we report the results of an experience conducted in a group of teachers of a religious institute, in which prayer was used as a technique to prevent burnout. Methods: 50 teachers and support staff employed at a Catholic school of a Congregation of nuns volunteered for this study. They were randomized into 2 groups: Prayer Treatment (PT) (n = 25) or control group (n = 25). The treatment protocol was based on the combination of individual Christian prayer and a focus group of prayer-reflection. The participants received two 30 min training sessions a week over two months. Job satisfaction, well-being and burnout symptoms (emotional exhaustion and depersonalization sub-scales) were measured at baseline and at follow-up (4 months) with the Italian versions of the Maslach Burnout Inventory (MBI) validated for teaching and education sector, the General Health Questionnaire (GHQ-30) and the Warr, Cook, and Wall's Job Satisfaction Scale. Results: At follow-up, a significant improvement of all outcome measures was observed. Emotional exhaustion (16.80 to 4.92, p < 0.001), Depersonalization (3.72 to 0.60, p <0.001) levels, psychological impairment (10.08 to 2.04, p< 0.001) were significantly decreased, job satisfaction (45.96 to 77.00, p< 0.001) was increased. The effect sizes (Glass’ Δ) of the therapeutic interventions ranged from 0.53 (satisfaction level) to 2.87 (psychological health), suggesting moderate to large effects. Discussion: Prayer could be effective, no less than meditation and other spiritual or mind-body techniques, in contrasting the negative effects of occupational stress and preventing burnout among teachers and, possibly, other human service professionals.